Propagation and control of shear waves in piezoelectric composite waveguides with metallized interfaces. (February 2017) - Piliposyan, D.G.; Piliposian, G.T.; Ghazaryan, K.B.
Abstract: This paper investigates coupled electro-elastic shear waves propagating along a piezoelectric finite width waveguide consisting of layers separated by metallized interfaces and arranged in a periodic way along the guide. The modified matrix method is applied to obtain the dispersion equation for a waveguide with straight walls. Bragg resonances and the presence of trapped modes and slow waves are revealed and analyzed for a periodic structure consisting of unit cells made up firstly from two different piezoelectric materials, and secondly from two identical piezoelectric materials. An analytical expression for the transmission coefficient for the waveguide with a defect layer is found that can be used to accurately detect and control the position of the passband within a stopband. This can be instrumental for constructing a tuneable waveguide made of layers of identical piezoelectric crystals separated by metallized interfaces.